2021
DOI: 10.1016/j.crtox.2021.02.006
|View full text |Cite|
|
Sign up to set email alerts
|

Using yeast two-hybrid system and molecular dynamics simulation to detect venom protein-protein interactions

Abstract: Highlights The venom protein-protein interactions in snake venom remain largely unknown. Y2H coupled with MD simulations was used to detect venom protein interactions. Venom PLA 2 s interact with themselves and Lys49 PLA 2 interacts with venom CRISP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…leveraged next‐generation sequencing technique that works together with Y2H to yield high‐resolution domain mapping of PPI [16], and Ying et al. applied molecular dynamics simulation on Y2H identified proteins to further reveal structural complexities of venom PPI [17].…”
Section: Experimental Methods For Ppi Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…leveraged next‐generation sequencing technique that works together with Y2H to yield high‐resolution domain mapping of PPI [16], and Ying et al. applied molecular dynamics simulation on Y2H identified proteins to further reveal structural complexities of venom PPI [17].…”
Section: Experimental Methods For Ppi Identificationmentioning
confidence: 99%
“…based on Y2H to further elucidate key aspects of PPI. Bacon et al developed a quantitative approach qYY2H to estimated protein-protein binding affinities [15]; Castel et al leveraged next-generation sequencing technique that works together with Y2H to yield high-resolution domain mapping of PPI [16], and Ying et al applied molecular dynamics simulation on Y2H identified proteins to further reveal structural complexities of venom PPI [17].…”
Section: 1mentioning
confidence: 99%
“…Similarly, exogenous substances can be added to improve the quality of some protein-rich products. MD simulation could be used to effectively observe the dynamic process of protein binding with exogenous substances, providing a supplement to the experimental conclusions ( Jia et al, 2021 ).
Fig.
…”
Section: Application Of Molecular Simulation In Foodsmentioning
confidence: 99%
“…Snake venoms are composed of a wide variety of bioactive substances—e.g., carbohydrates, inorganic elements, peptides, carboxylic acids, lipids, biogenic amines, purine nucleosides, and others—but 60–90% of them are proteins [ 3 , 4 , 5 , 6 ]. Some of these proteins have been described to form covalent and/or non-covalent complexes with other homologous and/or heterologous proteins [ 7 , 8 , 9 ], which possibly enhance the pathophysiological action of venoms to paralyze and kill preys. For example, in the rattlesnake Crotalus durissus terrificus venom, crotoxin (basic subunit) and crotapotin (acid subunit) form a heterodimeric complex, which dissociates after the complex reaches its target at the pre-synaptic membrane or the sarcolemma [ 10 ].…”
Section: Introductionmentioning
confidence: 99%